Co-LAEEBA: Cooperative link aware and energy efficient protocol for wireless body area networks. (October 2015) - Ahmed, S.; Javaid, N.; Yousaf, S.; Ahmad, A.; Sandhu, M.M.; Imran, M.; Khan, Z.A.; Alrajeh, N.
Highlights: Proposed model gives energy efficient communications for human body in WBAN. Link aware communications. Cooperative routing decreases path loss. Cooperative routing allows more frequent data gathering. Abstract: Performance evaluation of Wireless Body Area Networks (WBANs) is primarily conducted in terms of simulation based studies. From this perspective, recent research has focused on channel modeling, and energy conservation at Network/MAC layer. Most of these studies ignore collaborative learning and path loss. In this paper, we present Link-Aware and Energy Efficient protocol for wireless Body Area networks (LAEEBA) and Cooperative Link-Aware and Energy Efficient protocol for wireless Body Area networks (Co-LAEEBA) routing schemes. Unlike existing schemes, the proposed work factors in collaborative learning and path loss. Cost functions are introduced to learn and select the most feasible route from a given node to sink while sharing each others distance and residual energy information. Simulation results show improved performance of the proposed protocols in comparison to the selected existing ones in terms of the chosen performance metrics.